TINJAUAN YURIDIS KEWENANGAN PENGADILAN NEGERI DALAM MENYELESAIKAN SENGKETA BISNIS YANG MEMUAT KLAUSULA ARBITRASE - Rachmatika Lestari (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2019)
The provisions of Article 3 and Article 11 paragraph (1) and (2) of the Arbitration and APS Act gives authority to institute arbitration to resolve a dispute that has been established settlement through arbitration. But in reality, the judiciary in this case the District Court still examine the dispute and make a decision, although in the agreement have included the arbitration clause, such as the dispute between PT. Pertamina Hulu Energy Raja Tempirai (PHE RT) against PT. Golden Spike Energy Indonesia (GSEI). The main problem in this research is; (1) does the district court have the authority to examine and dispute the dispute in the event of an arbitration clause? and (2) in what cases have the district court authorized to adjudicate a business dispute containing an arbitration clause?. The purpose of this study is to identify and explain about authority and in terms of whether the District Court has the authority to examine, hear and decide disputes of business containing the arbitration clause. This study is a normative juridical research with the aim of studying the principles and rules contained in the science of law. The data used consist of primary legal materials, secondary legal materials and tertiary legal materials. Results showed that the Institute of Justice is required to respect the arbitration institution, the case that own the arbitration clause could not be submitted to the District Court, unless there Torts in terms of making the arbitration decision is unfounded in good faith. About the things that cause the District Court jurisdiction over business disputes containing the arbitration clause, among others, relating to the cancellation of the arbitral award on the basis of Torts in terms of making the arbitration decision is unfounded in good faith (Article 70 of the Arbitration and APS Act). Keywords: Authority of the District Court, Business Dispute and Arbitration Clause